Executive Functions and Quality of Classroom Interactions in Kindergarten Among 5–6-Year-Old Children - Veraksa, Aleksander; Bukhalenkova, Daria; Almazova, Olga (Frontiers in Psychology, 2020)
According to international longitudinal studies, the quality of preschool education is of great importance for the children further development. The modern research greatest interest in the field of studying the quality of preschool education is precisely the assessment of the relationship between the teacher and children as well as the teaching quality in kindergarten groups. In this regard, the Classroom Assessment Scoring System (CLASS) seems to be the one of the most relevant for the educational environment quality evaluation. The CLASS methodology (that includes emotional support, classroom organization and instrumental support) is based on the cultural-historical approach, that shows the interaction between students and adults as the main mechanism for child’s development. The aim of this study is to investigate the relationships between different aspects of the classroom organization quality in kindergarten group and executive functions components (such as cognitive flexibility, inhibitory control, working memory) in 5-6 years old children. The quality of classroom interaction was measured by the CLASS. The study used the DCCS method to assess cognitive flexibility; and NEPSY-II subtests «Inhibition» to assess inhibitory control, «Memory for Designs» and «Sentences Repetition» to assess visuo-spatial and verbal working memory respectively. The study was approved by the Ethics Committee of the Faculty of Psychology at Lomonosov Moscow State University. The study involved 26 kindergarten groups in Moscow. While conducting the research the extreme groups were identified (5 with low quality and 10 with high quality levels of classroom interaction. Then three kindergarten groups with low level (65 children) and three groups with high level (68 children) of interaction within classroom were selected and compared. The results revealed that children from groups with low level of classroom interaction quality have higher results in cognitive flexibility tasks when compared with children from groups with high level. Whereas children from groups with high classroom interaction quality levels demonstrate higher results in visuo-spatial working memory tasks and inhibitory control tasks as contrasted with children from low quality groups. These findings attest to the importance of classroom interaction quality for the executive functions development in the preschool age.